THE IMPACT OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, AND FOREIGN OWNERSHIP ON EARNINGS MANAGEMENT (Empirical Study on Consumer Non-Cyclicals Sector Companies Listed on the Indonesia Stock Exchange in 2021-2023) - Kadek Ayu Novita Permata Sari; Gede Juliarsa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Earnings management remains a common strategy employed by public companies, wherein management intentionally adjusts financial statements to meet targeted earnings. This research offers empirical insights into how managerial, institutional, and foreign ownership influence earnings management practices within consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange between 2021 and 2023. Profitability is considered as a control variable in the analysis. Adopting a quantitative associative approach and utilizing multiple linear regression, the study examines 23 selected firms through purposive sampling, yielding 69 total observations. The findings indicate that all three types of ownership exert a negative impact on earnings management, whereas profitability shows a positive effect. From a theoretical standpoint, the results reinforce agency theory, emphasizing that ownership structures function as effective oversight tools in curbing opportunistic managerial actions. In practical terms, the study’s outcomes provide valuable guidance for investors in evaluating financial reporting risks and motivate company management to uphold greater transparency and accountability.